New insights into the regulation of apoptosis, necroptosis, and pyroptosis by receptor interacting protein kinase 1 and caspase-8. (April 2020) - Schwarzer, Robin; Laurien, Lucie; Pasparakis, Manolis
Abstract: Necroptosis and pyroptosis are inflammatory forms of regulated necrotic cell death as opposed to apoptosis that is generally considered immunologically silent. Recent studies revealed unexpected links in the pathways regulating and executing cell death in response to activation of signaling cascades inducing apoptosis, necroptosis, and pyroptosis. Emerging evidence suggests that receptor interacting protein kinase 1 and caspase-8 control the cross-talk between apoptosis, necroptosis, and pyroptosis and determine the type of cell death induced in response to activation of cell death signaling.